Analisis Penempatan Pegawai terhadap Kinerja Pegawai (Di Sekretariat Dewan Perwakilan Rakyat Daerah (DPRD)) - Kadek Januarsa Adi Sudahrma; Komang Trisna Melia Antara (Journal of Economics and Management Scienties, 2023)
The purpose of placing employees in the secretariat of the Bali Provincial Dewan Perwakilan Rakyat Daerah (DPRD) in agencies/organizations will be more easily achieved if employees are placed in positions that are in accordance with their competencies. However, competence and ability alone are not enough to improve employee performance, accuracy is also needed in placing employees according to their competencies and abilities. The placement of employees in increasing work productivity in a company needs to be improved in education and training to support employee activities at the Bali Provincial DPRD Secretariat. Mastery of work in accordance with the work of each employee and in accordance with the skills, abilities, and skills still found neglected jobs, due to the inability of employees to occupy positions which ultimately did not match the targeted time. So the purpose of this study is to determine the placement of employees on employee performance. The method used in this research is descriptive qualitative where the researcher describes in detail and descriptively about the facts in the field. The results of this research are that every new employee must be included in training, so that all activities carried out by employees, both employees placed in the Public Relations section and other sections have attended training in order to improve the quality of products of the Bali Provincial DPRD Secretariat to achieve employee productivity levels.